The effect of using a site for a tutorial on the Internet for teaching mathematics Academic achievement in university (Journal of the College of Basic Education, 2022)
The research aims to know the use of an educational site on the Internet for teaching mathematics in the university academic achievement To test the research hypotheses, were provided an educational site on the Internet has been developed and tested Academic achievement was extracted Indications of sincerity and Reliability coefficient formed the research sample of (60) students, students from the first stage of the students of Yarmouk University - Department of Computer Science was divided into two groups (experimental group and control group). And the application of research procedures and the use of statistical treatments appropriate, the results of research that have been reached the following. The existence of statistically significant differences in academic achievement of university mathematics e attributed to the variable method of teaching through educational site on the Internet for the benefit of the experimental group, and also to the existence of differences attributable to sex variable for females, and the results showed that there were statistically significant differences (α = 0.05) in the academic achievement of university mathematics is due to the interaction between the variables of sex and method of teaching students. Researcher is recommended to create a design and provision of educational sites on the Internet for various topics in mathematics for all grades